PSMD14 Targeting Triggers Paraptosis in Breast Cancer Cells by Inducing Proteasome Inhibition and Ca2+ Imbalance - Lee, Hong-Jae; Lee, Dong-Min; Seo, Min-Ji; Kang, Ho-Chul; Kwon, Seok-Kyu; Choi, Kyeong-Sook (Multidisciplinary Digital Publishing Institute (MDPI), 2022)
PSMD14, a subunit of the 19S regulatory particles of the 26S proteasome, was recently identified as a potential prognostic marker and therapeutic target in diverse human cancers. Here, we show that the silencing and pharmacological blockade of PSMD14 in MDA-MB 435S breast cancer cells induce paraptosis, a non-apoptotic cell death mode characterized by extensive vacuolation derived from the endoplasmic reticulum (ER) and mitochondria. The PSMD14 inhibitor, capzimin (CZM), inhibits proteasome activity but differs from the 20S proteasome subunit-inhibiting bortezomib (Bz) in that it does not induce aggresome formation or Nrf1 upregulation, which underlie Bz resistance in cancer cells. In addition to proteasome inhibition, the release of Ca2+ from the ER into the cytosol critically contributes to CZM-induced paraptosis. Induction of paraptosis by targeting PSMD14 may provide an attractive therapeutic strategy against cancer cells resistant to proteasome inhibitors or pro-apoptotic drugs.